2006
DOI: 10.1210/jc.2005-1752
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged (48-Hour) Modest Hyperinsulinemia Decreases Nocturnal Heart Rate Variability and Attenuates the Nocturnal Decrease in Blood Pressure in Lean, Normotensive Humans

Abstract: Prolonged mild hyperinsulinemia disrupts the circadian rhythm of cardiac autonomic activity. Early changes in the neural control of cardiac activity may provide a potential mechanism mediating the pathophysiological link between impaired glucose tolerance and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…These data provide interesting insights into the consequences of prolonged mild elevations in plasma glucose and insulin such as may occur during overfeeding conditions on food intake, hunger and post-prandial responses to a test meal. The effects of the prolonged 48-h glucose infusion on the plasma insulin and glucose levels during the 48-h period have been previously reported but all other data presented in this paper are new 10 .…”
Section: Introductionmentioning
confidence: 54%
“…These data provide interesting insights into the consequences of prolonged mild elevations in plasma glucose and insulin such as may occur during overfeeding conditions on food intake, hunger and post-prandial responses to a test meal. The effects of the prolonged 48-h glucose infusion on the plasma insulin and glucose levels during the 48-h period have been previously reported but all other data presented in this paper are new 10 .…”
Section: Introductionmentioning
confidence: 54%
“…This is supported by the findings that experimentally evoked hyperinsulinemia decreases dipping among healthy and normal-weight adults. 8 In addition, adult non-dipper essential hypertensive patients had higher fS-insulin and P-glucose levels and a higher HOMA index than dipper patients. 20 In this study, we found no association between P-glucose and dipping.…”
Section: Discussionmentioning
confidence: 96%
“…Experimentally evoked hyperinsulinemia has been found to decrease dipping among healthy and normal-weight adults. 8 Among children, chronic poor glycemic control may place patients with type 1 diabetes at risk for higher nocturnal BP 4 and fasting insulin (fS-insulin) or HOMA is positively associated with sleep BP among obese children. 9 Obese, but otherwise healthy, adolescents are at higher risk of unfavorable glucose metabolism 10 as well as reduced nocturnal BP dipping 2 compared with normal-weight peers.…”
Section: Introductionmentioning
confidence: 99%
“…In normalweight and normotensive individuals short-term hyperinsulinemia, which is one of the features of pre-diabetes, was already able to induce a decrease in heart rate variability [53]. Hyperinsulinemia is one of the features of pre-diabetes and the possibility exists that the early impairement of the cardiovascular reflex function occurring in both IGT and hyperinsulinemia/insulinresistance may be the cross-bridge between the increased cardiovascular disease risk and the early changes in glucose tolerance [53].…”
Section: Impaired Autonomic Function In Metabolic Syndrome and Diabetesmentioning
confidence: 99%
“…Hyperinsulinemia is one of the features of pre-diabetes and the possibility exists that the early impairement of the cardiovascular reflex function occurring in both IGT and hyperinsulinemia/insulinresistance may be the cross-bridge between the increased cardiovascular disease risk and the early changes in glucose tolerance [53].…”
Section: Impaired Autonomic Function In Metabolic Syndrome and Diabetesmentioning
confidence: 99%